Peran Orang Tua Dalam Memberikan Pendidikan Seks Bagi Remaja di Desa Tasi Kecamatan Lembur Kabupaten Alor - Yessy Mata; Rosalia Owa Gadja (Jurnal Ilmiah Wahana Pendidikan, 2022)
The role of parents in providing sex education to adolescents has not been carried out properly. Parents have limited knowledge and understanding of sex education, making it difficult to explain in depth to adolescents. The research method used is descriptive research with a qualitative approach. The data collection techniques used were interviews, observation and documentation while the data analysis techniques were data reduction, data presentation, and drawing conclusions. The results of this study indicate that parents carry out their role in providing sex education for adolescents although not too broadly and maximally, namely as educators explaining what little they know about sex education such as changes in reproductive organs, wet dreams, puberty and sex problems; as an evaluator who checks and assesses children's understanding of the information conveyed about sex education that has been provided; as a companion who listens to and advises children; and as a monitor always control what children do